2013
DOI: 10.1103/physrevlett.110.106802
|View full text |Cite
|
Sign up to set email alerts
|

Bloch Model Wave Functions and Pseudopotentials for All Fractional Chern Insulators

Abstract: We introduce a Bloch-like basis in a C-component lowest Landau level fractional quantum Hall (FQH) effect, which entangles the real and internal degrees of freedom and preserves an Nx × Ny full lattice translational symmetry. We implement the Haldane pseudopotential Hamiltonians in this new basis. Their ground states are the model FQH wave functions, and our Bloch basis allows for a mutatis mutandis transcription of these model wave functions to the fractional Chern insulator (FCI) of arbitrary Chern number C,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
150
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 48 publications
2
150
0
Order By: Relevance
“…This approach relies on the relative angular momentum, which, in this case, is an exact quantum number. As such, it cannot be applied to the cylinder, torus, or any quantum Hall lattice model such as fractional Chern insulators, for which the analogue of pseudopotentials has been developed recently [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…This approach relies on the relative angular momentum, which, in this case, is an exact quantum number. As such, it cannot be applied to the cylinder, torus, or any quantum Hall lattice model such as fractional Chern insulators, for which the analogue of pseudopotentials has been developed recently [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The most striking features of FQH state are the topological ground state degeneracy on torus and the emerging quasiparticles obeying fractional statistics 1,2 . Recently, it has been demonstrated that FQH states can also be realized in various topological flat-band (TFB) models without Landau levels [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . In such an interacting system, an explicit demonstration of topological order and quasiparticle statistics is still highly desired, which has attracted lots of recent interests [22][23][24][25][26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…Since interactions on a lattice are intrinsically directional, FCIs can possess anisotropic PPs that are even larger than the isotropic ones. The PP decomposition of a FCI requires a basis mapping between the single-body orbitals of the FCI and FQH systems [39][40][41][42][43][44]. We adopt the mapping introduced in Ref.…”
mentioning
confidence: 99%